The translucent image of the National Stadium. Policies of the light in the representations of the Chilean catastrophe (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article takes up some discussions about photographic images to analyze the regime of visibility raised by the civic-military dictatorship in Chile. Our objective will be to present three ideas about images: the transparent, the opaque and the translucent, as strategies for thinking about the symbolic structure imposed by the authoritarian model and questioning the official propaganda mechanism proposed by the military. Along with this, taking as axis the mentioned categories, we will analyze the photographs that were captured by a powerful telephoto lens from a building near the first detention center, the National Stadium, in 1973.
Keywords: National Stadium, Photography, Memory, Dictatorship